Implementation of Health Protocol Policy as a COVID-19 Mitigation Effort at the DPR RI Complex in Senayan, Jakarta - Hanifa Muslimah, Rifa’at; Mukaromah, Nahdiyatul; Firdaus, Laila (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The COVID-19 pandemic caused a surge in COVID-19 cases at the House of Representatives of the Republic of Indonesia (DPR RI) building, necessitating the maximization of mobility restrictions within the DPR RI premises. Objective: This study aims to analyze the health protocol policy and the influencing factors on its implementation as an effort to mitigate COVID-19 at the DPR RI building. Method: This research uses a qualitative method with descriptive analysis, with data collected through observation, interviews, and documentation. The results of this study indicate that the implementation of health protocol policies within the DPR RI has been in place since March 2020. Result and Discussion: The implementation of health protocol policies to control COVID-19 at the DPR RI premises has been carried out since March 2020. The DPR RI Secretariat General has also issued appeals to comply with health protocols, and facilitated COVID-19 vaccination, antigen swab tests, and PCR tests for employees working at the DPR RI. Factors influencing the implementation of health protocol policies at the DPR RI include out-of-town and international visits by DPR members and their expert staff. Conclusions: Efforts in implementing health protocol policies at the DPR RI include consistent adherence to established health protocols to control the spread of COVID-19. Additionally, the Secretariat General provides facilities such as masks, hand sanitizers, vitamins, and medicines to all employees at the DPR RI building